Poly(lactic acid)/chitosan foams prepared by conventional method: Mechanical properties, cytotoxicity and in-vitro degradation - Pasuta Sungsee; Varaporn Tanrattanakul (Songklanakarin Journal of Science and Technology (SJST), 2020)
The present study evaluated the feasibility of using a conventionally prepared poly(lactic acid) (PLA) foam. A PLA foam was successfully prepared by compression molding. Azodicarbonamide was used as a chemical blowing agent. Chitosan was added as a bioactive material and poly(ethylene glycol) (PEG) was added as a plasticizer for PLA. Chitosan promoted the plasticization effect of PEG. The combination of chitosan and PEG contributed the lowest Tg and Tcc of PLA. The plasticized PLA showed greater impact strength than PLA. All foams showed closed-cell morphologies with relatively large pores. Chitosan and PEG reduced pore size and the reduction in pore size was greater when both additives were combined. Cytotoxicity was determined from MG-63 cell proliferation on samples, and all foams showed non-cytotoxicity. The addition of chitosan and/or PEG decreased weight loss of PLA in in-vitro degradation tests. This work was preliminary work and more studies need to be done.